KEPADATAN IKAN NAPOLEON (CHEILINUS UNDULATUS) DI PERAIRAN SINJAI DAN BONE-SULAWESI SELATAN - Syam, Amran Ronny; Mujiyanto, Mujiyanto (Perhimpunan Biologi Indonesia, 2014)
The exploitation of Napoleon fishery rates (Cheilinus undulatus) in the past year has been higher. Some areas inIndonesia are still doing the fishing business. Since the napoleon fish was registered in the IUCN red list &Appendix II of CITES, the export quota of 3,600 fishes per year was applied up to the year 2011. In order tosupport the evaluation size in the water bodies around Sinjai and Bone of the determination of napoleon fishprotection status, this study aims to determine fish population South Sulawesi. The method used was SnorkelingVisual Census (SVC). The results obtained indicate napoleon fish abundance is low (0 to 4 individuals/ha). Highestabundance of napoleon fish was found in Lapoipoi & Batanglampe, however none in three locations, i.e., Larearea,Pasiloange and Malambere. It is suggested that protection to species & its habitat is done in four locations wherethe napoleon fish were found, especially in Lapoipoi & Batanglampe.Keyword: napoleon fish, density, Sinjai, Bone, South Sulawesi